2021
DOI: 10.1016/j.bbrc.2021.09.023
|View full text |Cite
|
Sign up to set email alerts
|

The in vitro and in vivo efficacy of CT-P59 against Gamma, Delta and its associated variants of SARS-CoV-2

Abstract: The SARS-CoV-2 variant is rapidly spreading across the world and causes to resurge infections. We previously reported that CT-P59 presented its in vivo potency against Beta variants, despite its reduced activity in cell experiments. Yet, it remains uncertain to exert the antiviral effect of CT-P59 on Gamma, Delta and its associated variants (L452R). To tackle this question, we carried out cell tests and animal studies. CT-P59 showed neutralization against … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 19 publications
1
42
0
Order By: Relevance
“…Regdanvimab decreased viral load in the upper and lower respiratory tracts in animal models of SARS-CoV-2 infection [ 2 ]. The antibody showed antiviral activity against newly emerging variants of SARS-CoV-2 (Gamma, Delta and its associated variants [ 14 ] and 501Y.V2 or B.1.351 [ 15 ]). In vitro, regdanvimab was able to neutralize these variants, albeit showing reduced binding affinity to their RBD.…”
Section: Scientific Summarymentioning
confidence: 99%
See 1 more Smart Citation
“…Regdanvimab decreased viral load in the upper and lower respiratory tracts in animal models of SARS-CoV-2 infection [ 2 ]. The antibody showed antiviral activity against newly emerging variants of SARS-CoV-2 (Gamma, Delta and its associated variants [ 14 ] and 501Y.V2 or B.1.351 [ 15 ]). In vitro, regdanvimab was able to neutralize these variants, albeit showing reduced binding affinity to their RBD.…”
Section: Scientific Summarymentioning
confidence: 99%
“…In vitro, regdanvimab was able to neutralize these variants, albeit showing reduced binding affinity to their RBD. In transgenic mouse models inoculated with these variants, regdanvimab at clinically relevant dosages improved survival rate, reduced weight loss and decreased viral load in the upper and lower respiratory tracts [ 14 , 15 ].…”
Section: Scientific Summarymentioning
confidence: 99%
“…This lineage has been classified into three sublineages viz. B.1.617.1, B.1.617.2, and B.1.617.3 [34]. All the sublineages are found to be harboring Several studies have confirmed the role of this RBD-ACE2 interaction in the viral entry process [18][19][20].…”
Section: Introductionmentioning
confidence: 78%
“…This lineage has been classified into three sublineages viz. B.1.617.1, B.1.617.2, and B.1.617.3 [34]. All the sublineages are found to be harboring diverse mutations within the RBD of the S protein [32].…”
Section: Introductionmentioning
confidence: 98%
“…Ferrets are a suitable model of COVID-19 for features such as viral replication kinetics, virus dissemination and transmission compared to other small animal models [28, 29]. Clinical presentation is absent or mild, and histopathology findings usually show variable grades of inflammatory infiltration in the upper and/or lower respiratory tract, which is not homogeneous among reports [22, 30, 31]. However, a large share of these studies relate to the original strains of SARS-CoV-2, and little is yet known about the susceptibility of the ferret to VOCs.…”
Section: Discussionmentioning
confidence: 99%